Implementation of Community-based Environment Sanitation Program (Case Study in Benteng Sub-district, Kepulauan Selayar Regency, South Sulawesi Province) - Salihun, Gunawan (JPAS (Journal of Public Administration Studies), 2016)
Lack of clean water and sanitation infrastructure systems is a major problem in most developing countries. One of the policies implemented by the Central Government through the Ministry of Public Works is the Special Allocation Budget on Community-Based Environment Sanitation Program for domestic wastewater infrastructure, and drainage for the poor in rural areas or slums. The purpose of this study is to analyze implementation, supporting and inhibiting factors of community-based environment sanitation program in Kepulauan Selayar regency using a case study conducted in benteng sub-district. This study found that implementation of community-based environment sanitation program in benteng sub-district, Kepulauan Selayar Regency has been successfully implemented, but still found the inhibiting in the implementation. The successful implementation can be seen from the actors of this policy implementation completely carried out their duties and responsibilities, the funding and programs from regional government and central government, support the mechanism of the implementation run smoothly in accordance with the provision.Â